2015
DOI: 10.5194/hess-19-1753-2015
|View full text |Cite
|
Sign up to set email alerts
|

Storm type effects on super Clausius–Clapeyron scaling of intense rainstorm properties with air temperature

Abstract: Abstract. Extreme precipitation is thought to increase with warming at rates similar to or greater than the water vapour holding capacity of the air at ~ 7% °C−1, the so-called Clausius–Clapeyron (CC) rate. We present an empirical study of the variability in the rates of increase in precipitation intensity with air temperature using 30 years of 10 min and 1 h data from 59 stations in Switzerland. The analysis is conducted on storm events rather than fixed interval data, and divided into storm type subsets base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
166
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(176 citation statements)
references
References 56 publications
10
166
0
Order By: Relevance
“…These are all 10 min precipitation depths, with 0.1 mm resolution, measured over the exact same period with the same Lambrecht tippingbucket instruments, with standardized calibration and maintenance. These rainfall data are of very good quality and have recently been used in other studies of storm properties in Switzerland (e.g., Gaál et al, 2014;Molnar et al, 2015).…”
Section: Study Sites and Datamentioning
confidence: 99%
“…These are all 10 min precipitation depths, with 0.1 mm resolution, measured over the exact same period with the same Lambrecht tippingbucket instruments, with standardized calibration and maintenance. These rainfall data are of very good quality and have recently been used in other studies of storm properties in Switzerland (e.g., Gaál et al, 2014;Molnar et al, 2015).…”
Section: Study Sites and Datamentioning
confidence: 99%
“…The intensity of sub-daily precipitation extremes is more sensitive to temperature changes compared to the intensity of daily extremes (Westra et al 2014). CC scaling can be also affected by local and regional factors that can limit moisture availability, especially in mountain valleys (Molnar et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…There is observational evidence that extreme precipitation intensity has increased in many places (Trenberth et al 2003, Lende rink et al 2011, Benestad 2013, O'Gorman 2015, Molnar et al 2015 and climate simulations have revealed that this characteristic will be maintained and even intensified under future global warming (Pall et al 2007, Allan & Soden 2008, Scoccimarro et al 2013, Ban et al 2015. This behaviour is supported from a theoretical point of view by the so-called Clausius-Clapeyron relation (hereafter referred to as 'CC scaling'), which states that atmospheric humidity will increase at a rate that follows the saturation vapor pressure dependency on temperature (a rate of ~6−7% °C −1 ), under conditions of constant relative humidity (Trenberth et al 2003, Pall et al 2007, Westra et al 2014, Molnar et al 2015. A recent review on this topic is presented by O'Gorman (2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Wasko et al (2015) showed in a study conditioning the scaling on precipitation event duration that, in Australia, moisture availability limitations cannot be found for short events (1 h-2 h). In Switzerland, Molnar et al (2015) concluded that there could be limitations of moisture availability. However, this conclusion was drawn without discussing its dependence on the precipitation duration.…”
Section: Introductionmentioning
confidence: 99%